ANCIENT RUSSIA IN FOLK HISTORICAL REPRESENTATIONS OF RUSSIANS AND BELARUSIANS: COMMON AND SPECIAL - O. Matveyev (Гуманитарные и юридические исследования)
The article is devoted to a comparative analysis of the historical ideas of Russians and Belarusians about the heritage of Ancient Rus. With the reference to toponymic traditions and legends, epic plots, spiritual poems, ritual poetry, the author examines the peculiarities of the attitude of Russian and Belarusian peoples to the characters and events of ancient Russian history. The parallels are revealed in the responses to the activities of Prince Vladimir in strengthening the state unity of Russia, in comprehending the images of the Russian princesses Olga and Rogneda with the help of landscape elements, in the participation of the people in the recruitment of the squads. The images of heroes-snake-fighters are considered in the context of ideas about the opposition of Christianity and archaic beliefs in the era of Vladimir I and his successors. At the same time, the epic Volkh Vseslavievich was the personification of the legacy of pre-Christian Russia, the epic records of which were recorded in the northern Russian provinces until the middle of the 19th century, and the image of a werewolf prince was reflected in Belarusian fairy tales of that time. The reflection of traces of the dynastic ties of Ancient Russia with European states in the epic about Nightingale Budimirovich is considered in analogy with ritual texts, as all the main images, namely the arrival of a foreign groom from across the sea on ships, the construction of a "tower", the image of the groom as a nightingale in the bride's garden, the arrival of the bride in the golden-domed chambers of the groom and others, are represented in Russian and Belarusian wedding poetry. Based on the materials of toponymic legends, similar plots related to the Tatar invasion are characterized. The author sees the peculiarity of Belarusian historical ideas in the fact that the folk versions of history in the Aesopian language of fairy tales, spiritual poems, ritual poetry opposed the historical concepts of the invaders, the memory of the unity and greatness of Ancient Russia, praised the exploits of the ancient Russian heroes, substantiated the need to combat social and confessional oppression. Despite the difference in the historical conditions in which they were formed, the folk ideas of Russians and Belarusians, their plots and images are largely identical. Similar texts performed an integrating function, preserving the memory of heroes and devotees, endowed with typical features of a folk character. With all the generalizations, hy-perbolizations, local manifestations of identity, ethnocultural and confessional stereotypes, Russians and Belarusians did not distort the main meaning of their historical spirits.